The structure, conduct, and performance of the hatchery segment of the aquaculture value chain in Bangladesh - Ali, Hazrat; Belton, Ben; Haque, Mohammad Mahfujul; Murshed-e-Jahan, Khondker; Ignowski, Liz (Frontiers in Aquaculture, 2023)
Seed production has experienced significant growth in Bangladesh over the last decade, driven by the increasing number of hatcheries, but little is known about the organization and behavior of the hatchery segment of the aquaculture value chain. We conducted a comprehensive study with 66 hatcheries in southern Bangladesh between May and August in 2022 to address this gap. The major findings are as follows. (1) The number of hatcheries increased by 15% over the past decade, with a 27% increase in fish hatcheries and a 47% decrease in crustacean hatcheries. (2) Carp and tiger shrimp were the most commonly produced fish and crustacean seeds, contributing 67% and 99% of volume and 66% and 97% of sales value, respectively. (3) The hatcheries were family-owned and operated enterprise, and generated a total 2,491 full time equivalent (FTE) jobs. (4) Hatcheries used 86% of their broodstock annually and replaced them regularly for improving quality and avoiding inbreeding. (5) 18% of hatcheries reported facing diseases and/or water quality problems, but mean economic loss was only 0.71% of seed sales value, which is a low level of loss and waste. (6) Average annual net profit margin was relatively modest, averaging 54% of the gross revenue, which suggests the existence of competitive seed production and marketing. The results showed that the hatchery segment in southern Bangladesh appears to be dynamic, well developed, efficient, and relatively competitive.